Electro-optic response of bipolar nematic liquid crystal confined in oblate spheroid - Yang, Chenjing; Chen, Ran; Feng, Leyun; Zhang, Rui; Chen, Dong (Frontiers in Soft Matter, 2022)
Electro-optic response of liquid crystals (LCs) relies on the molecular reorientation of LCs under external electric field and is important for a wide spectrum of applications. Here, we uncover an interesting electro-optic response of 5CB nematic LC confined in an oblate spheroid and subjected to external electric field. Under the planar anchoring, the nematic LC spheroid adopts a bipolar structure with the bipolar axis lied in the horizontal film plane. When a threshold electric field EF, is applied, the bipolar structure reorients from the horizontal configuration (LC molecules align along long axis direction) to the vertical configuration (LC molecules align along short axis direction), involving the competition of elastic energy, surface anchoring energy and electric field energy. In contrast to bipolar nematic LC droplets, the vertical configuration does not relax to the low-energy horizontal configuration after removing E; we argue that is due to the oblate shape of the nematic LC spheroid, which traps the bipolar structure in a local energy minimum. We use continuum simulation to demonstrate the detailed response and the reorientation dynamics of bipolar nematic spheroids under E field, showing consistent results with the experiments and confirming the proposed switching mechanism. Nevertheless, the vertical configuration of the bipolar structure could relax to the low-energy horizontal configuration by thermal cycling. Our studies provide clear experimental results that show the characteristics of the electro-optic response of oblate LC spheroids, which have both fundamental and practical implications.